Application of Fish Index of Biotic Integrity (Fish-IBI) for Quality Evaluation of Nong Han Wetland - Rayan, Somsak; Ngamsnae, Praneet (Rajamangala University of Technology Tawan-ok Research Journal, 2020)
The application of fish index of biotic integrity (Fish-IBI) to evaluate the effect of anthropogenic stress on fish assemblage integrity and quality of Nong Han wetland, Sakon Nakhon, Province, was conducted by using fish data gathered from the previous studies from year 1968 to year 2005. Fish-IBI scores were designed from separate assemblage metrics in main four categories based on taxonomic richness, habitat composition, trophic composition, fish health and abundance guilds, and total 12 metrics were constructed as the reference conditions. Then, the fish data of this study, surveying from March 2011 to February 2012, were used as dataset for all metrics with the criteria and score range of 5-3-1 system. Ten metrics from Karr (1981) were adopted viz., number of native species, %dominant species, number of intolerant species, %tolerant individual, %omnivorous individual, %benthic invertivores, %specialist carnivores-tolerants, number of late maturing species and %anomalies. Two new modified metrics: number of benthic species and number of water column species were added retaining 12 original metrics. The fish data of this study reported that 16,073 fish specimens, consisting of 16 family and 52 species, which were examined by 12 metrics. The total Fish-IBI score of 38 was calculated, which ranked as fair level. This score indicated that the anthropogenic stress was increasing, evidenced by decreasing number of fish and the ratio of tolerance and omnivore, whereas the percentage of tolerant species, and %individual as increased. This study suggested that fish index of biotic integrity concept is acceptable, some modifications of metrics are necessary for fish community in the tropical water bodies.